Study on the mechanical performance of a three-layered wire rope strand with a surface pit in varied corrosion direction into the wire. (June 2022) - Chen, Yuanpei; Wang, Qing; Qin, Wei; Xiang, Jian
Highlights: The mechanical property of a corroded three-layered wire rope strand is analysed. The severest stress concentration and plastic strain occur in the corrosion pit. The corrosion pit weakens the contact property and bearing capacity of the strand. The pit with smaller axial inclined angle causes worse performance of the strand. The two types of inclined angles have opposite effects on mechanical properties. Abstract: Pitting corrosion often occurs in wire rope strands under harsh service environments, causes material removal and local stress concentration, and has been an important trigger for the failure of the strands. In this paper, the spatial parameter equations of wires in each layer of a three-layered wire rope strand with a corroded outermost wire are derived. Based on the equations, the high-precision finite element model of the corroded strand with varied corrosion direction into the wire is established with the consideration of the elasto-plasticity of the wire material. Then axial tensile simulations of the strand are performed to analyze the influence of the surface pit on the mechanical properties, including the contact characteristics, the stress-strain characteristics, the elastoplastic characteristics and the axial load-bearing characteristics, of the strand. The results show that the stress concentration is obvious in the corrosion area, and the maximum stress and plastic strain of the strand occur in the pit. The existence of corrosion pit decreases the bearing capacity of the strand, while increases the contact pressure, von Mises stress, and equivalent plastic strain of the strand significantly. The maximum von Mises stress, maximum plastic strain, stress concentration factor, maximum contact pressure and the decrement of bearing capacity increase with increasing circumferential inclined angle of the pit, while decrease with increasing axial inclined angle of the pit.